Implementasi model pembelajaran circ berbantuan media strip story dalam pembelajaran menulis teks narasi di sekolah dasar - Imtihan Syarifatul Ula; Rukayah Rukayah; Septi Yulisetiani (Universitas Sebelas Maret, 2025)
This research aims to explore (1) the utilizing of the CIRC learning model with strip story media in learning to write narrative texts for class IVA students of MIS Muhammadiyah Sidowayah, (2) narrative text writing skills of class IVA students of MIS Muhammadiyah Sidowayah who learn using the CIRC model and strip story media. This study is a qualitative study with a case study method. The data sources in this study are teacher, students, learning processes, and narrative text documents. Data collection techniques use observation, interviews, and documentation studies. The data validity test technique in this study uses time triangulation and technique triangulation. The data analysis technique uses an interactive model, namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this study are as follows. First, the implementation of learning to write narrative texts using the CIRC learning model and strip story media that the teacher did has fulfilled all stages, including orientation, organization, concept introduction, exploration and application, publication, and closing. In the exploration stage of learning, the teacher uses strip story learning media to help students come up with ideas for writing narrative texts. Second, the narrative writing skills of class IVA students who learned using the CIRC learning model and strip story media were quite good. The skill with the highest percentage was the ability to arrange the sequence of narrative texts based on the time of the incident. The lowest writing ability was the accuracy of the use of punctuation in sentences.